2017
DOI: 10.1021/acs.chemmater.6b04508
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Free-Standing Ultrathin Two-Dimensional PbS Nanocrystals with Efficient and Highly Stable Dielectric Properties

Abstract: Two-dimensional (2D) materials with downscaled thicknesses are the quest of the electronics industry because of their immense potential in modern microelectronics. Despite the discovery of several novel 2D materials, the flexible design of highperformance free-standing ultrathin 2D dielectric nanocrystals (NCs) with a large planar morphology remains the most challenging task. We develop a method for synthesizing high-quality free-standing ultrathin 2D NCs of PbS with a well-defined large rectangular morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 62 publications
(107 reference statements)
2
30
0
Order By: Relevance
“…To achieve absorption in the SWIR, narrow band gap materials 7,8 have to be used. PbS nanosheets 9,10 have been synthetized 11,12 and show tunable absorption 13 almost up to the bulk band gap value. 14 They also present a large lateral extension [15][16][17] (up to several µm) which is of great interest for the design of single-particle devices such as field effect transistors 18,19 (FETs) and photodetectors.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve absorption in the SWIR, narrow band gap materials 7,8 have to be used. PbS nanosheets 9,10 have been synthetized 11,12 and show tunable absorption 13 almost up to the bulk band gap value. 14 They also present a large lateral extension [15][16][17] (up to several µm) which is of great interest for the design of single-particle devices such as field effect transistors 18,19 (FETs) and photodetectors.…”
Section: Introductionmentioning
confidence: 99%
“…[ 214 ] It is noteworthy that free‐standing ultrathin 2D PbS nanocrystals prepared using the same method were assigned to the rock‐salt phase in another work. [ 215 ] A comparison of the XRD results revealed that the crystal phase is more likely to be an orthorhombic phase. This material exhibits efficient and highly stable dielectric properties.…”
Section: Group Iv–vimentioning
confidence: 99%
“…[1][2][3][4][5][6] However,t he conditions suitable for nucleationg rain in uniform solutionm ight not be suitable for tuning the size and shape of nanocrystals. [1][2][3][4][5][6] However,t he conditions suitable for nucleationg rain in uniform solutionm ight not be suitable for tuning the size and shape of nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal semiconductor nanocrystals have attracted considerable attention due to their unique size‐ and shape‐dependent optical and electronic properties. During the past decades, researchers have made great effort to synthesize semiconductor nanocrystals with controllable size and shape, in order to explore their application in light emitting diodes, solar cells, and so on . However, the conditions suitable for nucleation grain in uniform solution might not be suitable for tuning the size and shape of nanocrystals .…”
Section: Introductionmentioning
confidence: 99%